PENERAPAN SISTEM INFORMASI AKUNTANSI PENGELOLAAN KEUANGAN BERBASIS WEBSITE - Weiskhy Dharmawan (Jurnal Sistem Informasi Akuntansi, 2023)
The Foundation is one of the organizations engaged in religious education and social welfare, as well as its work in the community has contributed greatly to the development and progress of society with its good roles in the field of religious and social education and providing facilities and infrastructure for the community. community needs, especially in the development of Islamic boarding schools. Where the researcher takes part of the management sistem in the form of input data, output data and the preparation of financial reports in financial management in question is the financial management of the TPA and Baitul Mall, TPA and Baitul Mall are the management of donations from the community. The current financial management sistem is still carried out in the conventional way, namely the recording of input data, output data and the preparation of financial reports are still carried out one by one, causing inaccuracies and also resulting in time delays. The meaning of input data and output data are cash inflows and cash out transactions which are still recorded in the general cash book. So that in this financial recording process, it will cause difficulties in recording and most likely will be vulnerable to losing files in the form of records of cash income and expenditure transactions and difficulties in determining profit and loss so that it takes time to make financial records into the general cash book. so the author has the idea to design a financial recording application in the form of a web-based financial management accounting information sistem so that incoming and outgoing transaction data is stored in an online database and financial information can be known quickly and accurately for the owner of the Foundation.